Three coins in the fountain [videorecording (DVD)] - Patrick, John, 1905-1995; Webb, Clifton, 1889-1966; McGuire, Dorothy, 1918-2001; Peters, Jean, 1926-2000; Jourdan, Louis; McNamara, Maggie, 1928-1978; Brazzi, Rossano, 1916-1994; St. John, Howard, 1905-1974; Givney, Kathryn, 1896-1978; Nesbitt, Cathleen, 1888-1982; Young, Victor, 1900-1956; Krasner, Milton; et al. (Studio classic, 2004)
Three American women working in Rome, Italy, share a spacious apartment and the desire to find love and marriage, each experiencing a few bumps in their journeys to romance.